Comparison of cefamandole nafate to cefamandole by microbiological assay. - Winely, C L (1979)
Before microbiological assay, cefamandole nafate should be hydrolyzed for 1 h at 37 degrees C in pH 8 buffer (0.1 M) or for 30 min at room temperature in aqueous solutions containing 1.25 molar equivalents of sodium carbonate.